(untitled) (Indian Journal of Animal Production and Management, 2024)
The present study was conducted to seek herbal alternatives and nutritional modulation to solve the problem of coccidiosis, a deadly protozoan disease of broilers. For the purpose, an experiment of 35 days’ duration (days 0-21 pre-infection period and days 22-35 post-infection period) was conducted to test the efficacy of herbal/natural products/dietary nutrients for the management of mixed coccidial infection prevalent under field conditions. For this purpose wheat grass juice, chelated mineral supplement, herbal anticoccidial and seeds of Embelia ribes without and with sodium bicarbonate, organic chromium, herbal vitamin E-Selenium without and with organic chromium were used to study the immunological parameters of un-infected and infected broilers with 60,000 sporulated oocysts of mixed Eimeria species. Results of the experiment revealed that LST in terms of delta optical density of T- and B-cells was maximum in wheat grass juice while ELISA titre against Newcastle Disease was maximum in herbal vitamin E-Selenium group. All the types of dietary modulation were found to be effective up to different extent in the management of poultry coccidiosis. Further research should focus on micro-array and proteomic technologies to solve the problem.